“Your house looks like that show…”: exploring consumers’ perceptions towards media-inspired home décor - Mulla, Tausif; Kaluvilla, Bincy Baburaj; Zahidi, Farah; Al Sabbah, Saher; Tantry, Ansarullah (Frontiers in Computer Science, 2025)
IntroductionThe growing popularity of media-inspired home décor, where consumers draw aesthetic influence from movies and television shows, reflects a broader cultural shift in how individuals personalize their living spaces. While this trend has gained traction globally, limited research has explored the motivations and experiences of consumers, particularly among expatriates living in multicultural contexts such as the United Arab Emirates (UAE).MethodsThis study adopts a qualitative research design, utilizing semi-structured interviews with 15 expatriates from diverse professional and cultural backgrounds residing in the UAE. The collected data were analyzed using thematic analysis to uncover underlying motivations, perceptions, and challenges associated with media-inspired home décor.ResultsThe analysis revealed six prominent themes: media-inspired self-expression, where participants used décor to communicate personal identity; aesthetic and emotional motivations that drive design choices; financial accessibility and creative adaptations that enable consumers to achieve desired looks within budget constraints; social validation and peer influence that shape décor decisions; risks of themed décor including potential drawbacks and limitations; and artistic engagement and cultural appreciation that demonstrates deeper connections with media content. Participants expressed strong connections between media-inspired décor and identity construction, emotional fulfillment, and cultural expression.DiscussionThe findings indicate that media-inspired home décor is a meaningful avenue for consumers to construct and communicate their identities while navigating practical limitations and evolving design trends. This study highlights the significance of symbolic and emotional drivers in consumer behavior and provides practical insights for interior designers, marketers, and home décor brands aiming to engage with culturally diverse and media-savvy audiences.